Black beauty - Sewell, Anna (London, Jarrold & Sons., 1877)
Black Beauty is a powerful and touching story told from the perspective of a horse named Black Beauty. The novel chronicles his life from a peaceful upbringing in the English countryside to the hardships he faces as he is passed from one owner to another. Along the way, Black Beauty experiences both kindness and cruelty, reflecting on the treatment of horses and the responsibilities of their human caregivers. The book is a plea for compassion and animal welfare, highlighting themes of empathy, dignity, and the impact of humane care.
Keywords: black beauty, novel; Animal welfare, moral responsibility